2007
DOI: 10.1111/j.1365-2559.2007.02662.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and biological significance of cytokeratin 19 in pancreatic endocrine tumours

Abstract: CK19 expression correlates with patient survival only when detected with the RCK108 antibody and mainly in insulinomas. Ki67 index and metastases represent the only two independent predictors of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 24 publications
2
38
3
Order By: Relevance
“…Although the literature reports discordant opinions on the value of tumour proliferation markers in predicting a patient's prognosis, many studies have shown that Ki-67 expression in histological sections obtained from PETs is an important predictor of their biological behaviour (Pelosi et al 1992, 1996, Rindi et al 1998, Rigaud et al 2001, Butturini et al 2006, La Rosa et al 2007, Vilar et al 2007. The WHO classification of PETs includes Ki-67 expression in the list of parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the literature reports discordant opinions on the value of tumour proliferation markers in predicting a patient's prognosis, many studies have shown that Ki-67 expression in histological sections obtained from PETs is an important predictor of their biological behaviour (Pelosi et al 1992, 1996, Rindi et al 1998, Rigaud et al 2001, Butturini et al 2006, La Rosa et al 2007, Vilar et al 2007. The WHO classification of PETs includes Ki-67 expression in the list of parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Ki-67 is one of the criteria used to grade PETs according to the WHO classification (De Lellis et al 2004). Although recent studies have shown that the expression of cytokeratin 19 (CK 19) predicts long-term survival among patients with PETs (Deshpande et al 2004, La Rosa et al 2007), this marker is not yet widely used in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Positive staining for CK19 was shown to be a powerful prognostic factor predicting shorter survival, even after controlling for variables such as the number of mitoses, tumor necrosis, and Ki-67 expression (Deshpande et al 2004). CK19 may not be predictive of survival in patients with non-functional PETs (La Rosa et al 2007). Expression of CD10 has also been shown to predict worse survival, and a correlation was found between CD10 expression and the WHO classification where the more malignant tumors were more likely to express CD10 (Deschamps et al 2006).…”
Section: Other Prognostic Factorsmentioning
confidence: 99%
“…A reason for the discrepancy between these studies could be the use of different CK19-directed monoclonal antibodies and/or criteria for evaluation of immunostaining results. We have used the RCK108 clone, which is used by the most other studies and shown to be more reliable for CK19 analysis than the BA17 clone (La Rosa et al 2005).…”
Section: Y M H Jonkers Et Al: Predictors Of Survival In Eptsmentioning
confidence: 99%